Evaluation of Three Hydration Strategies in Detection Dogs Working in a Hot Environment - Otto, Cynthia M.; Hare, Elizabeth; Nord, Jess L.; Palermo, Shannon M.; Kelsey, Kathleen M.; Darling, Tracy A.; Schmidt, Kasey; Coleman, Destiny (Frontiers in Veterinary Science, 2017)
Physical activity in hot environments can increase the risk of heat stress or heat stroke in dogs. Heat tolerance is influenced by acclimatization to the environment, physical fitness and hydration state. Three common strategies to promote hydration in working dogs are free access to water, oral electrolyte solutions and administration of subcutaneous fluids. None of these methods have been compared for safety or efficacy in a working environment. In a cross-over design, 7 vehicle-screening canines were randomly assigned to each of the 3 hydration strategies during working shifts at the Sarita, TX checkpoint. Physical, behavioral and biochemical parameters were collected before, during and after a work shift (mean 5.7 +/- 0.8 hours). Dogs were given 10 ml/kg oral water (W), 10 ml/kg chicken flavored oral electrolyte solution (OES), or 15 ml/kg of subcutaneous fluids (SQ) initially followed by controlled access to water or OES. The dogs drank 15.61 ± 4.47 ml/kg/hr of water and OES when in the OES group, compared to 7.04 ± 3.42 mls and 5.56 ±4.40 of water, for the water and SQ groups respectively. The median environmental temperature was 84.8F (29.3C). The median humidity was 70%. Based on mixed effects linear modeling, dogs in the OES and SQ groups had significantly higher total CO2, and lower packed cell volume and total plasma protein at the end of the day. Creatinine increased a small but significant amount in the SQ group and decreased in the OES group. Searching behaviors were independent of hydration strategy but highly related to the dog specific factors of sex, breed and activity level. Under conditions of controlled activity in moderate heat and humidity, dogs accustomed to the work and the environment were more likely to increase fluid consumption and hydration when provided a flavored OES. Potential benefits of OES and SQ were indirect and no adverse effects were documented for any of the hydration strategies tested.